Pullout Characteristics of Geosynthetics Reinforced Earth Using Multilayer Spreading Pullout Test. (18th June 2017) - Park, Jong-Beom; Kim, Daehyeon; Yang, Si-Bong; Kim, Jang-Heung
Abstract : Pullout test equipment for examining pullout characteristics in a reinforced earth structure is relatively larger than direct shear testing machines and requires much time and expenses in preparing samples. Moreover, because of irregular stress distributions with respect to the length of reinforcements, it is difficult to analyze pullout test results. In this study, we developed a multilayer spreading pullout apparatus enabling the pullout test in the order of a top stage, middle stage, and bottom stage with different loads once a ground model is prepared, suggesting an efficient method of a multilayer spreading pullout test. The pullout test is carried out at least three times with the prepared ground model while changing confining loads. Jumunjin sand was used to verify the developed pullout test apparatus and to analyze pullout characteristics of each reinforcement. The analysis reveals that the difference between angles of pullout friction is approximately 0.86 to 1.3° which is distributed within the error range of a pullout test. As a result, the multilayer spreading pullout apparatus is applicable as a new pullout apparatus, and the suggested method of multilayer spreading pullout test is identified as a pullout test technique efficiently to obtain pullout parameters.